Indigenous Peoples, Indigenous Knowledge and Their Issues on Climate Change, particularly on REDD+, in Developing Countries - Maharjan, Shree Kumar; Maharjan, Keshav Lall (International Journal of Applied Sciences and Biotechnology, 2017)
The lands, territories and resources of indigenous peoples (IPs) have been of significant historical importance to their livelihoods, cultures and spiritual identities. Over 370 million indigenous peoples are currently living in 70 countries in the world, mostly in remote, ecologically fragile and marginalized areas that are rich in traditional skills, knowledge and practices. Climate change is a global issue, impacting all livelihood sectors at the national and local levels. The poor and marginalized people, especially indigenous peoples, Dalits and women are in the forefront of its vulnerability and impacts. These people and communities have made the lowest contributions to the greenhouse gases emissions, however, they are the most at risks to its impacts. Furthermore, the policies and programs often marginalize and sideline the voices and issues of these people. This paper attempts to gather, review and analyze the information on indigenous knowledge, issues of indigenous peoples on climate change particularly in REDD+ in developing countries. The paper aims to highlight the REDD+ process in Nepal, its obligations at the national and international level (with cases from Asia, Africa and Latin America) and the indigenous perspectives towards the issues, gaps and challenges within the national and international negotiations. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 273-283